Light-Fidelity (LiFi) – Innovative Technology to Transform Healthcare Industry - Johnson, Bijoy (BMH Medical Journal - ISSN 2348–392X; Vol 10 No 4: October-December 2023, 2023)
In the rapidly advancing digital world, technology is revolutionizing the healthcare industry. Light-Fidelity (LiFi) is emerging as the next-generation communication technology with several benefits including high data rates. LiFi is a high-speed communication technology that can transmit data at the speed of light. LiFi is a cutting edge wireless networking that uses infrared and visible light spectrum data exchange. The concept of visible light communication is used to achieve secure, bi-directional and fully networked wireless communications. It is a fundamental 5G technology. Unlike other technologies like ethernet, there is no intrinsic capacity limit for LiFi. It can provide point-to-point communication at very high data rates.